ANALYSIS OF THE TRAINING OF APPLICANTS FOR EDUCATION AT THE DEPARTMENT OF PEDIATRIC THERAPEUTIC DENTISTRY BASED ON THE RESULTS OF THE INTEGRATED TEST EXAM «KROK» - L.I. Amosova; L.F. Kaskova; O.S. Pavlenkova; L.P. Ulasevych; O.Yu. Andriyanova; M.O. Sadovski; O.V. Khmil (Український стоматологічний альманах)
The quality of medical education is largely determined by the objectivity and accuracy of its control systems. There is a global trend towards the use of a standardized testing system for medical students at the state level with the use of closed multiple-choice tests. Given the ever-increasing importance of the integrated test exam “Krok 2”, its main indicators in the dynamics were analyzed and a comparative analysis with the results of the subtest in pediatric therapeutic dentistry was carried out.